এমাজউদ্দীন আহমদ সংবর্ধনা গ্রন্থ - শিকদার, আবদুল হাই; বড়ুয়া, সুকোমল; নাজনীন, দিল রওশন জিন্নাত আরা; পারভেজ, মাহফুজ (ঢাকা : শিকড়, 2011)
Articles on the life and works of Emajuddin Ahamed, educator and professor from Bangladesh; commemorative volume.
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Ahmed, Emajuddin; Educators -- Bangladesh -- Biography; College teachers -- Bangladesh -- Biography